Conversion Rate: Digital Analytics on Online Food Delivery Platform Customers - Margarena, Agung Novianto; Malina, Mayang Hema; Arum, Maliana Puspa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The purpose of this research is to analyze the factors that cause conversion rate. This research combines attributes from Pee et al (2018), Cho (2015) and Kapoor dan Vij (2018) as a novelty in the model development base for measuring conversion rates. This research is classified as descriptive quantitative research with a sampling technique using snowball sampling of 110 respondents who use online food delivery (OFD) applications in Surakarta City. The results showed that collaborative design and delivery service had a significant effect on conversion rate. While visual design, information, and navigation attributes do not have a significant effect on conversion rate. This study recommends application service providers to improve cashback money, points, and order tracking services.